Experimental study of slip-in haunched gusset plate connection for double lipped cold-formed steel section - Firdaus M.; Saggaff A.; Tahir M.M.; Ngian S.P.; Aminuddin K.M.; Usman F.; Saloma (International Journal of Scientific and Technology Research, 2023)
Connections on the cold-formed steel (CFS) section become an interesting topic concerning its failure mode that the thin-walled behaviour controls it. CFS weakness is usually caused by early local buckling and local instability. The bolt connections and t he gusset plate are the easy way to install a joint of steel structures on CFS application. This study is aimed to investigate the behaviour of the CFS connection of double lipped channel C-sections of C20019 for the beam and C30024 for the back-to-back column with a slip-in haunched gusset plate. The haunched gusset plate is S275 steel grade, 6 mm thickness connected with M12 bolt. The experiment was carried out by isolated joint test to acquire moment capacity and rotation of the connection. It is observed that the connection failure modes were on the beam bolt and the local buckling on the column flange. The existence of the slip-in gusset plate reduces the buckling effect induced by the behaviour of the thin plate. The moment of joint (Mj) obtained from the experiment was 20 kNm, the stiffness (Sj) was 250 kNm/rad, and the rotation at the final load was 0.079 radian. The comparison moment of joint by analytical and experimental was 0.78, while the ratio of stiffness was 2.04. The analytical and experi mental comparison between moment of joint and moment resistance of beam was 0.55. It concluded that the connection was categorized as partial strength and ductile connection for cold-formed steel section application. IJSTR 2019.